Current factors affecting feeder cattle pricing in Kansas and Missouri cattle markets - K.W. Harborth; L.L. Schulz; Kevin C. Dhuyvetter; Justin W. Waggoner (Kansas Agricultural Experiment Station Research Reports, 2010)
Today's tough economic environment for cattle producers makes each decision critically important, and increased knowledge of the link between pricing and genetic, management, and marketing decisions can increase an operation's sustainability and profitability. Cow-calf producers and cattle feeders have long been interested in the impact of various physical and market characteristics on feeder cattle and calf prices. As demonstrated in many previous studies, significant relationships exist between feeder cattle prices and their physical and market characteristics. Weight, lot size, health, condition, fill, muscling, frame size, breed, time of sale, and horn status significantly affect feeder cattle auction prices. Historically, significant premiums and discounts have been associated with these particular feeder cattle physical characteristics. The purpose of this study was to gain knowledge of the current link between market pricing and genetic, management, and marketing decisions. Findings from this research will provide updated information regarding how the myriad of industry changes since the 1980s and 1990s has affected the characteristics that influence feeder cattle and calf prices.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Feeder cattle prices; Premiums; Muscling; Breed; Frame size